Mothers' profile, food beliefs and practices in relation to pre-schoolers' nutritional status (2006)
This study investigated the socio-economic characteristics, food practices and food beliefs of mothers as well as the nutritional status of their pre-schoolers in five private pre-schools in Muñoz, Nueva Ecija, Philippines. A total of 130 mothers and 130 preschoolers served as respondents. Results showed that majority of mother respondents were 32 years and below, married and lived with their husbands. Mothers' educational attainment indicated 65 percent college graduate, 33 percent finished high school and only two percent completed their elementary education. Slightly over 70 percent of the mothers' belonged to the mean income group of Php 12,229.29 and below and 90 percent had 1-4 children and dependents. The type of employment varied from housewife to private, self and government employment. Almost 35 percent were housewives. The levels of food practices were categorized into meal regularity, meal preparation and meal service. Slightly more than half of the mothers scored "good" in food preparation while majority scored "fair" in meal regularity and meal service and "moderate" in food beliefs. Educational attainment was found to be significantly related to meal service and food beliefs, while gross family income was also found to be significantly related to meal service and meal preparation. About 48 percent of the pre-schoolers had normal weight; 73.8 percent had normal height and none of them was severely underweight. The educational attainment and gross family income were significantly associated with the weight for age of the pre-schoolers. In terms of mothers' food practices only meal preparation was significantly related to weight for age of the pre-schoolers; and only gross income and meal preparation were positively related to the weight for age of the pre-schoolers. Gross family income and meal preparation were also found to be significantly related to height for age of the pre-schoolers.
Keywords: Preschool children -- Nutrition